Development of Food Security Management Model through PAIC Process - Tumpracha, Kruemas; Thiengkamol, Nongnapas; Thiengkamol, Chatchai (Richtmann Publishing, 2012)
During the past few decades, Thailand has agricultural development policy that has emphasized on the nation’s foodsecurity and export income. It is also a food surplus country at the macro level, but at the household level remains a problem infood security. According FAO, food security refers availability, accessibility and utilization, especially, nutritional knowledge andunderstanding. But in the educational institute like as school, it should pay attention to quantity, quality, safety, and good tastewhich is the concept Ministry of Public Health of Thailand. Therefore, the upper secondary school students in NortheasternRegion, lack of nutritional knowledge, attitude, awareness, value and behavior. The objective of this research was to developfood security management model for upper secondary school student.The integrative method research was done participatoryaction research with Participatory Appreciate-Influence-Control technique (PAIC) and qualitative with focus group discussion.Populations were upper secondary school students of academic year 2012 of Kalasin Province. The sample was selectedaccording to purposive sampling technique. The questionnaire and evaluation forms were be used as tool for data collection.PAIC was implemented with the integration of SWOT analysis and brain storming during the training process. One -Way-ANOVA, and t-test were used for data analysis. The research results illustrated that before and after PAIC process implemented,the mean scores of posttest of environmental education process covered knowledge of food security management, nutritionalknowledge, proper consumption behavior, and training achievement were higher than pretest with statistical significance (p< .01,p< .01, p< .01, and p< .01). Three Dimensional Evaluation was employed for determination the perceptions of 48 uppersecondary school students in three aspects evaluation of Self-evaluation, Friend-evaluation, and Facilitator-evaluation by usingOne-way ANOVA in order to investigate the participation of upper secondary school students showed that there were nodifference of mean scores about participation in training process through brain storming with statistical significance (p>.05).